PENGARUH DOSIS PUPUK ORGANIK AMPAS TEBU DAN VOLUME PENYIRAMAN AIR TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT DI PRE-NURSERY - Ahmad Fahroji Sinaga; Ety Rosa Setyawati; Wiwin Dyah Ully P (Agros Journal of Agriculture Science, 2023)
Production waste that uses sugarcane plants if left unchecked will cause bad things to the environment and chemical fertilizers that are increasingly expensive make it more difficult for farmers. This study aims to determine the effect of the dose of bagasse organic fertilizer and the volume of water sprinkling on the growth of oil palm seedlings in the pre-nursery. The method used was a factorial experiment arranged in a completely randomized design (CRD) which consisted of two factors, the dose of bagasse organic fertilizer which consisted of 3 levels, namely control, 200 g, 300 g, and the volume of water sprinkling consisted of 4 levels, namely 100 ml. , 150 ml, 200 ml, 250 ml. research data were analyzed by means of variance at a significant level of 5%, data that were significantly different were further tested with a DMRT of 5%. The results showed that there was no significant interaction between the dose of bagasse organic fertilizer and the volume of water sprinkling on the growth of oil palm seedlings in the pre-nursery. Dosage of organic bagasse fertilizer did not significantly affect the growth of plant height, number of leaves, leaf area, stem diameter, root fresh weight, root dry weight, fresh plant weight and dry weight of oil palm seedlings in pre-nursery. This shows that bagasse organic fertilizer can be a substitute for inorganic fertilizers. Giving a dose of 200 g of organic bagasse fertilizer gave the best effect on the growth of the root length of the oil palm seedlings in the pre-nursery. The volume of water sprinkling treatment had no effect on all parameters except plant height. A watering volume of 150 ml is the most efficient volume and is sufficient for the high growth of oil palm seedlings.INTISARILimbah produksi yang menggunakan tanaman tebu jika dibiarkan akan menyebabkan hal buruk bagi lingkungan serta pupuk kimia yang semakin mahal membuat petani semakin kesulitan. Penelitian ini bertujuan untuk mengetahui pengaruh dosis pupuk organik ampas tebu dan volume penyiraman air terhadap pertumbuhan bibit kelapa sawit di pre-nursery. Metode yang digunakan yaitu percobaan faktorial yang disusun dalam Rancangan Acak Lengkap (RAL) yang terdiri dari dua faktor, dosis pupuk organik ampas tebu yang terdiri dari 3 aras yaitu kontrol, 200 g, 300g, dan volume penyiraman air terdiri dari 4 aras yaitu 100 ml, 150 ml, 200 ml, 250 ml. data hasil penelitian dianalisis dengan sidik ragam pada jenjang nyata 5%, data yang berbeda nyata diuji lanjut dengan DMRT 5%. Hasil penelitian menunjukkan tidak ada interaksi nyata antara dosis pupuk organik ampas tebu dengan volume penyiraman air terhadap pertumbuhan bibit kelapa sawit di pre-nursery. Pemberian dosis pupuk organik ampas tebu tidak memberikan pengaruh nyata terhadap pertumbuhan tinggi tanaman, jumlah daun, luas daun, diameter batang, berat segar akar, berat kering akar, berat segar tanaman dan berat kering tanaman bibit kelapa sawit di pre-nursery. Hal ini menunjukkan pupuk organik ampas tebu bisa menjadi pengganti pupuk anorganik. Pemberian dosis pupuk organik ampas tebu 200 g memberikan pengaruh terbaik terhadap pertumbuhan panjang akar bibit kelapa sawit di pre-nursery. Perlakuan volume penyiraman air tidak berpengaruh pada semua parameter kecuali tinggi tanaman. Volume penyiraman 150 ml adalah volume terefisien dan sudah cukup untuk pertumbuhan tinggi bibit kelapa sawit.